Advances in systemic treatment for adults with moderate-to-severe atopic dermatitis - Yung-Tsu Cho; Chia-Yu Chu (Wolters Kluwer Medknow Publications, 2019)
Atopic dermatitis (AD) is generally considered a T-helper type 2-dominated disease. Adult AD is often more severe and less manageable by topical therapies and may require systemic immunosuppressants that bear notable side effects and organ toxicities. There is an unmet need for safe and effective long-term therapy in this population. Dupilumab, a fully human monoclonal antibody, dually inhibits interleukin (IL) IL-4 and IL-13 signaling and has demonstrated promising efficacy and acceptable safety profile in several Phase III trials, followed by recent Food and Drug Administration approval for the treatment of moderate-to-severe AD in adults whose disease is inadequately controlled with topical therapies. Dupilumab may also serve as a new treatment option when other systemic medications have failed or are inadvisable. Nevertheless, long-term safety data beyond 1 year and comparison with the existing therapies remain to be investigated. Other emerging agents targeting pruritogenic proteins, chronic inflammation, and epidermal hyperplasia are under vigorous clinical development. In particular, nemolizumab, blocking IL-31-mediated pruritus, has been reported in Phase II trials to provide symptom relief by interrupting the itch-scratch cycle. Accompanied by thorough characterization of different phenotype and endotype subsets, the era of precision medicine could bring new prospects in the optimal treatment of AD.